Effect of Different Vane Combinations on Fertilizer Distribution Uniformity with Various Flow Rates in Spinning Disc Broadcasters - Mazhar Kara; Yıldıran Yıldırım (Journal of Agricultural Sciences)
Vanes throwing the particles of fertilizer or granular material onto a field are one of the most important machine parts influencing the fertilizer distribution pattern in spinning disc broadcasters.  Manufacturers prefer mostly straight-shaped vanes in spinning disc broadcasters, probably because their production is easy. In previous studies, therefore, many researchers studied the spinning disc broadcaster with the straight-shaped vanes only. In this study, the effect of the combinations of the straight-shaped vane with different shaped vanes on the fertilizer distribution uniformity in single-spinning disc broadcaster was investigated with various flow rates using triple superphosphate. The combinations used in the study were the straight-shaped vane in combination with forward-curved-5, forward-curved-10, back-curved-5, and back-curved-10 vane, and ‘no combination’ consisted of the straight-shaped vane only. The circular orifices of 30, 40, and 50 mm diameters were used at the bottom of hopper to obtain the different flow rates of the fertilizer. The results of the study showed that the combination of the different shaped vanes on the spinning disc had a significant effect on fertilizer distribution uniformity. ‘No combination’ used commonly in practice did not give the best fertilizer distribution uniformity. The best fertilizer distribution uniformity was obtained from the combination of the straight-shaped vane with forward-curved-5 vane shape for all the flow rates. The CV values obtained from this combination were 10.31%, 15.49%, and 19.92% for the orifices with diameters of 30, 40, and 50 mm, respectively.